Students' emotional intelligence and their attitudes towards creativity interferences: Lithuanian and Latvian case - Petkevičiūtė, Nijolė; Balčiūnaitienė, Asta; Ābele, Lilita; Adamonienė, Rūta (Landscape Architecture and Art, 2024)
Emotional Intelligence (EI) has been an important and controversial topic in recent decades. The level of emotional intelligence and creativity among students is an essential dimension of a successful study process, a topic that has not been sufficiently explored. This study, however, is a groundbreaking attempt to investigate this relationship among Landscape Architecture students in Lithuania and Latvia. Creativity, the skill to find new and valuable ideas to react to challenges, problems or needs, is a crucial aspect of this process. Moreover, creativity can usually be a new combination of known knowledge. Different generations are creative but should have a better background and theoretical understanding of emotional intelligence. This understanding is lacking, and this study aims to fill this gap. On the other hand, different generations look at the same reality from various perspectives. Therefore, the study seeks to look at the creativity interferences from the student’s point of view. The pilot study, conducted using a questionnaire created by the authors, aims to determine the peculiarities of student’s creativity interferences for their successful studies. It also analyses the theoretical background of emotional intelligence and creativity proposed by the scientific literature. It determines students’ level of emotional intelligence that would enhance their creativity to manage creativity interferences in achieving success during the study process.